ANALISIS BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PADA RESTORAN HARRIS SUITES FX SUDIRMAN JAKARTA PUSAT - Angela Merici Kurnia Nette; Sofiani Sofiani (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to analyze the effect of brand awareness on purchasing decisions for Harris Suites FX Sudirman restaurants. This study uses a survey type of research. The population in this study were consumers of the Harris Suites FX Sudirman restaurant. The sample used is consumers who know the existence of the Harris Cafe brand. The sampling technique used in this study was slovin with a sample size of 399 respondents. The technique used has been tested for validity, reliability test and data collection using a questionnaire that has been tested for validity and using data analysis techniques using simple regression tests. The results showed that there was a positive and significant influence on brand awareness (X) with purchasing decisions (Y)